Environmental context influences visual attention to responsible drinking messages - Daniel Frings; Antony C. Moss; Ian P. Albery; Guleser Eskisan; Thom Wilcockson; Alexander P. Marchant (2017)
Aims: Responsible drinking messages (RDMs) are used as a key tool to reduce alcohol-related harms. A common form of RDM is in a poster format displayed in places such as bars, bus stops and toilet cubicles. However, evidence for the effectiveness of RDMs remains limited. Moreover, it is not known how environmental contexts (e.g. the number of alcohol-related cues in the environment) impact how such RDMs are interacted with, nor how this in turn affects their efficacy. Methods: One hundred participants completed a pseudo taste preference task in either in a bar laboratory (alcohol cue rich environmental context) or a traditional laboratory. The walls of the laboratory displayed either RDM or control posters during this task and eye tracking was used to assess participant attention to the posters. Results: Participants looked at the RDM posters less in the bar laboratory where the environmental context is rich in alcohol cues compared to a traditional laboratory where alcohol cues are sparse. Neither poster type or environmental context affected the amount of 'alcohol' consumed and the amount of visual attention given to RDMs was unrelated to the amount of 'alcohol' consumed. Conclusions: These findings provide experimental evidence that RDMs do not influence drinking behaviour in the direction intended (reduced consumption in situ). In addition, locating RDMs in alcohol-cue rich environments may result in sub-optimal behavioural responses to the RDM materials (e.g. visual attention to content). To maximize the potential impact of RDMs, the optimal location for RDMs is in environments where pre-existing alcohol cues are sparse to non-existent. Short Summary: Responsible drinking messages (RDMs) aim to reduce alcohol consumption, however, the findings of this study show that they may not influence in situ consumption. These findings also suggest that the optimal location for RDMs is in environments with few or no other alcohol-related cues.